An inguinal hernia or a greater saphenous vein aneurysm? A case report - Seyhan Yılmaz; Sabür Zengin; Fatma Gürgen; Feryaz Kızıltan (Veins and Lymphatics, 2019)
Superficial venous aneurysms, which are mostly asymptomatic and detected when patients were referred to for the treatment or evaluation of a femoral or inguinal hernia or soft tissue masses, are associated with a risk of developing pulmonary embolism. We aimed to present a case of a greater saphenous vein aneurysm of which its misdiagnosis possesses morbidity risk and confused with inguinal hernia. A 45- year-old female patient admitted to our clinic with swelling and pain in her right groin that had been present for about three years. The patient was also treated with inguinal hernia repair once due to her related complaints. A venous color doppler ultrasound was performed for differential diagnosis and a 70x31-mm sized fusiform proximal greater saphenous vein aneurysm and a grade-4 pathologic reflux in the right saphenofemoral junction was observed in the ultrasonographic examination. As a result, the swelling detected in the inguinal region should be evaluated in terms of possible superficial venous aneurysm, which may cause thromboembolism and ruptures, and this condition, which is frequently confused with inguinal hernia, should be taken into consideration and taken under operation as soon as possible in case of its presence.